CHRONIC HEPATITIS B AND C IN WOMEN: COURSE OF PREGNANCY, DELIVERY AND MORPHOLOGICAL CHARACTERISTICS OF THE PLACENTA - M. A. Belopolskaya; V. Yu. Avrutin; E. A. Rukoiatkina; A. V. Dmitriev (Архивъ внутренней медицины, 2018)
Despite the widespread prevalence of chronic hepatitis all over the world, the impact of these diseases on the pregnancy course and on the childbirth is still insufficiently investigated. Recently, some  studies have been published, discussing the relationship between the state of the placenta and the risk of the mother to child transmission of hepatitis. The aim of this work was to make a comparative  analysis of the features of pregnancy in women with chronic  hepatitis B and C (CHB and CHC, respectively), to evaluate the  relationship between inflammatory changes in the placenta and the  frequency of hepatitis markers detection in cord blood. In this work  we present a retrospective analysis of the birth histories of randomly selected women with chronic hepatitis which gave birth in  the maternity hospital No. 16 in St. Petersburg. In total, 35 pregnant women with CHB and 36 pregnant women with CHC were included in this study. Excluded from the study were women with co-infections,  cirrhosis and severe concomitant diseases. The studied groups had  no significant differences in the age, weight and height, as well as in  the number of pregnancies and childbirths in the anamnesis.  According to the results of our study, there were no significant  differences in the state of newborns from the mothers with CHB and  CHC. According to our data, anemia during pregnancy occurred  significantly more frequently in women with CHB than with CHC. It  has been shown that in both groups, the choriodeciduitis was observed in almost a half of the women. Remarkably, the frequency of premature rupture of membrane in both groups was significantly  higher than the average in the population. In addition, a reliable  relationship between inflammatory changes in the placenta and the  detection of HBsAg in the cord blood was revealed. This relationship  suggests that in women with inflammatory changes in the placenta,  the risk of hepatitis B vertical transmission may be higher.